Examining the relationship between mothers' prenatal mental health and demographic factors with postpartum depression - Maryam Ghaedrahmati; Ashraf Kazemi; Gholamreza Kheirabadi; Masood Bahrami; Amrollah Ebrahimi (Wolters Kluwer Medknow Publications, 2018)
BACKGROUND AND AIM: Prenatal mental health has been shown to be related with postpartum depression. However, the role of mental and psychological factors in postpartum depression requires especial attention. Furthermore, the relationship between demographic factors and postpartum depression is contradictory. The study was aimed to identify role of prenatal anxiety and depression and demographic factors with postpartum depression. MATERIALS AND METHODS: A prospective cohort study was conducted with 303 pregnant women who have gestational age from 28 to 36 weeks and referred to health-care centers in Isfahan city and follow-up for 6-12 weeks after postpartum. Data were collected using the demographic form, Edinburgh depression, and anxiety Spielberger questionnaire during pregnancy and Edinburgh depression inventory in the 6th and 12th weeks after childbirth. Descriptive statistics and linear logistic regression were used to analyze the data. In demographic factors, data were analyzed using the Student's t-test, Chi-square, Pearson and Spearman test and after the meaningfulness of regression was used. RESULTS: Results showed that the 6 and 12 weeks after childbirth, 61 patients (20/1%) and 33 patients (10/9%) had postpartum depression. The most important risk factors for depression in the first 6 weeks were history of infertility (confidence interval [CI]: 0.56-0.767) (P = 0.018) and history of depression (CI: 1.155-1.369) (P = 0.000) and in 12 weeks, postpartum were history of depression (CI: 0.072-1.305) (P = 0.001). CONCLUSION: Infertility and history of depression during pregnancy were two risk factors of postpartum depression which should be taken into consideration during prenatal care.